Exploring the gap between diagnostic research outputs and clinical use of OCT for diagnosing glaucoma. Issue 8 (15th November 2019) - Michelessi, Manuele; Quaranta, Luciano; Riva, Ivano; Martini, Enrico; Figus, Michele; Frezzotti, Paolo; Agnifili, Luca; Manni, Gianluca; Miglior, Stefano; Posarelli, Chiara; Fazio, Stefano; Oddone, Francesco
Abstract : Aims: To explore the gap between diagnostic research outputs and clinical use of optical coherence tomography (OCT) in glaucoma and assess the reliability of a specific reference database when applied to a morphological imaging parameter for diagnostic purposes. Methods: Consecutive subjects enrolled in the Multicenter Italian Glaucoma Imaging Study (MIGIS) have been included in this cross-sectional, comparative evaluation of diagnostic tests study. Patients underwent measurement of global and sectorial peripapillary retinal nerve fibre thickness (pRNFL) and minimum rim width (MRW) by OCT. The sensitivity and specificity of reference-database categorical classifications were calculated by means of 2×2 tables and sensitivity was compared with that of the corresponding continuous parameter extracted from the receiver operating characteristic (ROC) curves by matching the specificity. Results: 280 Caucasian subjects have been included. At matched specificities, the sensitivity of pRNFL categorical classifications was statistically similar to that of the corresponding continuous parameters, whereas the sensitivity of the MRW categorical classifications was significantly lower than that of the corresponding continuous parameters. Conclusions: The diagnostic accuracy of reference database classifications might be lower than that extrapolated from the ROC curves of continuous parameters used in diagnostic research. The gap between the accuracy of these two approaches may be used to estimate the reliability of a specific reference database when applied to a continuous parameter for diagnostic purposes.